Didang Tang alleviates neuronal ferroptosis after intracerebral hemorrhage by modulating the PERK/eIF2α/ATF4/CHOP/GPX4 signaling pathway - Lu, Jing; Xu, Hanying; Li, Li; Tang, Xiaolei; Zhang, Ying; Zhang, Dongmei; Xu, Peng; Sun, Liwei; Wang, Jian (Frontiers in Pharmacology, 2024)
Ferroptosis is a crucial process contributing to neuronal damage following intracerebral hemorrhage (ICH). Didang Tang (DDT), a traditional therapeutic, has been used clinically to manage ICH for many years, yet the molecular mechanisms by which by DDT protects neurons from ferroptosis after ICH remain elusive. This study utilized high-performance liquid chromatography-based fingerprint analysis to characterize DDT's chemical composition. An ICH rat model and hemin and erastin-induced PC12 cell ferroptosis models were developed to investigate DDT's neuroprotective mechanisms. Histological assessments of brain tissue morphology and iron deposition were performed using hematoxylin-eosin, Nissl, and Perl's blue staining. Neurological function was evaluated using Longa and Berderson scores, while lipid peroxidation was measured using biochemical assays and flow cytometry. Protein expression levels of ferroptosis-and endoplasmic reticulum stress (ERS)-related markers were analyzed via Western blotting and immunofluorescence. Our results demonstrated that DDT reduced hematoma volume, decreased iron deposition, lowered malondialdehyde (MDA) levels, and upregulated glutathione peroxidase (GPX4) and SLC7A11 expression in affected brain regions. Furthermore, DDT downregulated GRP78 expression and inhibited the PERK/eIF2α/ATF4/CHOP/GPX4 pathway, exerting strong neuroprotective effects. The fluorescence staining results of MAP2/GPX4 and MAP2/CHOP suggested that DDT may regulate neuronal ferroptosis and ERs to exert the protective effect. In vitro experiments using hemin-and erastininduced neuron-derived PC12 cells as neuronal ferroptosis models developed in our laboratory corroborated these in vivo findings, showing increased survival and reduced lipid peroxidation in DDTtreated cells, along with similar inhibitory effects on ferroptosis and ERS. Molecular docking suggested that DDT components, such as sennoside B, amygdalin, rhein, and emodin, interact favorably with PERK/eIF2α/ATF4/CHOP signaling pathway proteins, highlighting their potential role in DDT's antiferroptosis effects. Overall, this study provides novel insights into DDT's protective mechanisms against ICH-induced neuronal injury by modulating ferroptosis and ERS pathways, underscoring its potential as an effective therapeutic strategy.